Angiotensin-Receptor Blocker, Angiotensin-Converting Enzyme Inhibitor, and Risks of Atrial Fibrillation: A Nationwide Cohort Study. Issue 20 (May 2016) - Hsieh, Yu-Cheng; Hung, Chen-Ying; Li, Cheng-Hung; Liao, Ying-Chieh; Huang, Jin-Long; Lin, Ching-Heng; Wu, Tsu-Juey
Abstract : Abstract: Both angiotensin-receptor blockers (ARB) and angiotensin-converting enzyme inhibitors (ACEI) have protective effects against atrial fibrillation (AF). The differences between ARB and ACEI in their effects on the primary prevention of AF remain unclear. This study compared ARB and ACEI in combined antihypertensive medications for reducing the risk of AF in patients with hypertension, and determined which was better for AF prevention in a nationwide cohort study. Patients aged ≥55 years and with a history of hypertension were identified from Taiwan National Health Insurance Research Database. Medical records of 25, 075 patients were obtained, and included 6205 who used ARB, 8034 who used ACEI, and 10, 836 nonusers (no ARB or ACEI) in their antihypertensive regimen. Cox regression models were applied to estimate the hazard ratio (HR) for new-onset AF. During an average of 7.7 years' follow-up, 1619 patients developed new-onset AF. Both ARB (adjusted HR: 0.51, 95% CI 0.44–0.58, P  < 0.001) and ACEI (adjusted HR: 0.53, 95% CI 0.47–0.59, P  < 0.001) reduced the risk of AF compared to nonusers. Subgroup analysis showed that ARB and ACEI were equally effective in preventing new-onset AF regardless of age, gender, the presence of heart failure, diabetes, and vascular disease, except for those with prior stroke or transient ischemic attack (TIA). ARB prevents new-onset AF better than ACEI in patients with a history of stroke or TIA (log-rank P  = 0.012). Both ARB and ACEI reduce new-onset AF in patients with hypertension. ARB prevents AF better than ACEI in patients with a history of prior stroke or TIA.